Deviant Behavior in Madam Gie's Cosmetics - Fitri Ramadhani; Sabda Dian Nurani; Adisty Yulia Rangkuti; Aidil Hazman Caniago; Gresia Findriany Sihotang; Tiara Ulina br Ginting (PT FORMOSA CENDEKIA GLOBAL, 2023)
Madame Gie, a cosmetics company, faces challenges in selling its products which occupy the third lowest position compared to its competitors. This study aims to investigate the impact of deviant behavior on consumer health caused by exposure to mercury in Madame Gie's cosmetic products. The research method used was laboratory analysis to identify the mercury content in Madame Gie's cosmetic products as well as interviews with a number of consumers who experienced negative health effects after using these products. The results showed that Madame Gie's cosmetic products contained levels of mercury that exceeded the safe limits set by regulatory bodies. Exposure to mercury in these products has a negative impact on consumer health, such as skin irritation, hormonal disturbances, and damage to the nervous system. Deviant behavior in the use of hazardous materials such as mercury in Madame Gie's cosmetic products is a violation of business ethics and can endanger the health of consumers. This research provides a better understanding of the possible consequences of deviant behavior in the cosmetics industry.